Association between injuries and occupational exposures in South Africa: an epidemiological study at the population level - Kinoti, Mary Kanyua (My University, 2012)
Introduction: Work - related injuries are of major public health importance because they have severe negative economic and social impacts to individuals, families, and a country’s economy as a whole. South Africa is a rapidly expanding economy and so there is great potential for workrelated injuries. Notably, a number of studies on work-related injuries in South Africa and globally are done at the industry level. While no effort to minimise occupational injuries at the enterprise level should be spared, more information is also required on the morbidity burden of these work-related injuries at the general population level. It was therefore against this background, that this research project was carried out. Objective: The objective of this study was to determine the association between injuries and occupations among workers aged 15 - 65 years. Methods: The dataset for this dissertation was extracted from the South African 2001 Labour Force Survey. Only respondents who reported having worked in the previous twelve months were included in the study sample (n=21,751). The outcome variable was injury over the previous twelve months. The explanatory variables were socio-demographic, occupation, and occupationally related characteristics. Logistic regression controlling for the socio-demographic characteristics was used to identify occupational and occupationally related predictors for incidence of injury at 95% confidence level. Results: Injury incidence of 4% (894/ 21751) was reported which was mainly associated with age, gender, ethnicity and province of residence at p<0.05. Male workers were more likely to sustain accidents than female workers with a risk ratio of male/female of 2.4 times. Unexpectedly, injuries increased with age. In respect to ethnicity, the Coloureds, Indian/Asians and Whites were 18%, 48% and 44% less likely to sustain injuries respectively compared to the vi African blacks while workers in the group called “Other” were 5.3 times at risk than African blacks. Adjusted analyses indicated that, workers in mining and quarrying (AOR=2.2), crafts and related trade (AOR=4.0), plant and machine operators (AOR=4.4) and elementary occupations (AOR=2.7) were predisposed to a higher risk of sustaining injury than other occupations. Surprisingly, permanent workers, those with written contract, pension contribution were found to have a higher likelihood of sustaining injuries than their counterparts. Conclusions: The incidence of injury to workers in South Africa was found to be at 4%. The older, male, and permanently employed workers were at a greater risk of sustaining injuries compared to young, female and casual workers respectively. In regards to occupations, mining and quarrying, crafts and related trade and elementary occupations elevated the risk of sustaining injuries than other occupations. It is highly recommended that occupation-specific programmes be instituted to minimise worker injuries particularly among the high risk work places. Further research is also required to investigate findings that were found to be inconsistent with existing literature namely; increase of injuries with increase in age, and why workers on permanent versus casual employment were more likely to sustain injuries.
M.Sc. (Med.) (Epidemiology and Biostatistics), Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: occupational injuries